The Synergistic Effect between Antibiotics and Biosynthesized ZnO Nanoparticles (Journal of the College of Basic Education, 2022)
The effect of ZnO nanoparticlesbiosynthesized by probiotics bacteria, Lactobacillus gasseri, Leuconostoc mesenteroides ssp.dextranicum and Lactococcus lactis ssp. lactis combined with different antibiotics were investigated against MDR skin infection causative bacteria. The diameter of inhibition zones (mm) around the different antibiotic discs including (10) from different classes of antibiotic which include Imipenem,Ceftazidime,Cefotaxime,Carbencillin,Aztreonam, Amikacin,Ciprofloxacin,Norfloxacin, Tetracycline and Oxytetracycline, with and without ZnO nanopatrticles against isolates were measured. The bactericidal actions of some antibiotics have been elevated in the presence of (subMIC) biosynthesized ZnONPs against some skin infection causing bacteria. The results of the study showed the synergistic effect of ZnO nanoparticles with antibiotics used in study on the bacterial isolates of Pseudomonas aeruginosa, Klebsiella pneumoniae, Acinetobacter baumanii and Staphylococcus aureus.